Komitmen Beragama dalam Pendidikan Islam Berbasis Masyarakat Mahasiswa STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur - Dian Febrianingsih; Arih Merdekasari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2018)
Abstract : This study aims to describe and analyze 5 things, 1) factors that influence the religious commitment of students in implementing community-based Islamic education, 2) forms of community-based Islamic education by students, 3) the impact of community-based Islamic education for students, and 4 ) psychological dynamics of religious commitment of STIT Islamiyah student KP Paron Ngawi in implementing community-based Islamic education. To answer the above problem, the researcher uses qualitative method with case study. Data were collected by in-depth interviews, participatory observation and documentation. The next data is analyzed with Miles & Hubberman concept which include data reduction, data exposure and conclusion. The form of community-based Islamic education conducted by the students is education diniyah non-formal path that is TPA and / or boarding. Implementation of TPA and pesantren have a positive impact on personal and social life on the whole subject. On the other hand, there is no negative impact of the activity on students. The dimensions of religious commitment consisting of dimensions of belief, ritual, knowledge, experience and belief; have varying degrees of influence on the subjects. Based on this there is a unique dynamics of religious commitment to each subject in the implementation of community-based Islamic education